The Economics of the Brain Drain Turned on its Head - Oded Stark (Annual World Bank Conference on Development Economics, Europe 2003 : Toward Pro-Poor Policies - Aid, Institutions, and Globalization, 2004)
When productivity is fostered by an individual's own human capital as well as by the economy-wide average level of human capital, individuals under-invest in human capital. A strictly positive probability of migration to a richer country raises both the level of human capital formed by optimizing individuals in the home country and the average level of human capital of non-migrants in the country. Conditions are provided under which the welfare of all workers is higher with migration than in its absence. A well-controlled, restrictive migration policy can enhance welfare and nudge the economy toward the social optimum.
Keywords: 330